The Problematics of Management Personal Protection Equipment Waste related to Covid-19 in Indonesia - Muhammad Hadin Muhjad; Fakhruddin Razy; Ahmad Fikri Hadin (Sriwijaya Law Review, 2021)
Medical Waste for Covid-19 Personal Protective Equipment (PPE) is classified as B3, which can potentially be a medium for spreading the virus. Therefore, management must be carried out, consisting of collection, sorting, transportation, temporary storage, to processing (destruction) based on the Circular of the Minister of Environment and Forestry Number 2 of 2020 using the incinerator and problematic autoclave methods. The purpose of this study is to find out how the law regulates the management of Covid-19 PPE waste in Indonesia and how it should be. The research method used is normative legal research. The results showed that based on the Circular Letter of the Minister of LHK No. 2 of 2020, it is determined that the destruction of Covid-19 PPE waste as B3 waste must go through an incinerator facility with a minimum combustion temperature of 800⁰ C and an autoclave equipped with a shredder. This method is considered overkill and incurs high costs. The conclusion of this study is to provide input for the Government to review or revise the Circular regarding safer Covid-19 PPE B3 waste management, including through the pyrolysis method.